Effect of Ball Size on Nanostructured Copper-tungsten Carbide Composite Prepared by Mechanical Alloying (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
In this study, nanostructured copper tungsten carbide composite was produced by mechanical alloying. Mechanical alloying was carried out by milling of copper (Cu), tungsten (W) and graphite mixture at 40 h with milling speed of 400 rpm in planetary ball mill using two different ball sizes. The crystallite size of the powder milled with 10 mm ball is smaller than 20 mm ball due to higher collision frequency. Lower expansion of Cu lattice was found for the powder milled with 20 mm ball than that of 10 mm ball. The composite obtain by milling with 20 mm ball had produced greater impact energy that facilitated the formation of tungsten carbide (WC).
Keywords: Copper-based composite; Mechanical alloying; Nanostructured materials; Ball size